NKG2D and its ligands: active factors in the outcome of solid organ transplantation? - Suárez-Álvarez, Beatriz (Nature Publishing Group, 2011)
The role of natural killer (NK) cells in solid organ transplantation is not well established, although several recent reports highlight the importance of the activating receptor NKG2D and its ligands in the development of rejection during transplantation. The human NKG2D ligands (MICA and MICB) are induced in allografts during acute and chronic rejection, and the presence of anti-MICA antibodies is correlated with a higher incidence of rejection. The binding of these ligands to its receptor NKG2D activates NK cells, enhances the functions of effectors, and allows NK cells to function as a bridge between innate and adaptive immunity associated with the transplantation. In fact, blockage of NKG2D with the anti-NKG2D monoclonal antibodies prolongs graft survival and prevents CD28-independent rejection in heart and skin allograft mouse models. Furthermore, the current immunosuppressive therapies can modulate the expression of NK cell receptors and consequently the effector functions of NK cells. That is particularly important during the first few months after transplantation, when the susceptibility to opportunistic viral infections is higher and NKG2D has an essential role. In this review, we analyze in detail the potential role of the NKG2D-activating receptor and its ligands in the immune responses during the outcome of solid organ transplantation. These findings open a new pathway for therapeutic intervention that can contribute to tolerance in solid organ transplantation.